2002
DOI: 10.14310/horm.2002.1170
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in patients with thyroid disorders

Abstract: Thyroid disorders are known to influence lipid metabolism and are common in dyslipidemic patients. Overt and subclinical hypothyroidism have an adverse effect on the serum lipid profile that may predispose to the development of atherosclerotic disease. Although thyroid substitution therapy is beneficial for patients with overt hypothyroidism, the question of whether subclinical hypothyroidism must be treated remains unanswered. The association between thyroid autoimmunity and lipoprotein (a) levels is controve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 54 publications
2
53
1
2
Order By: Relevance
“…Therefore, hypothyroidism constitutes a significant cause of secondary dyslipidemia. 15 From this study it is evident that hypothyroidism is associated with lipid disorders characterized by normal or slightly elevated cholesterol levels, increased LDL cholesterol and lowered HDL cholesterol. Early detection and treatment of dyslipidemia in hypothyroid patients will attenuate cardiovascular risk and improve general well being.…”
Section: Discussionmentioning
confidence: 71%
“…Therefore, hypothyroidism constitutes a significant cause of secondary dyslipidemia. 15 From this study it is evident that hypothyroidism is associated with lipid disorders characterized by normal or slightly elevated cholesterol levels, increased LDL cholesterol and lowered HDL cholesterol. Early detection and treatment of dyslipidemia in hypothyroid patients will attenuate cardiovascular risk and improve general well being.…”
Section: Discussionmentioning
confidence: 71%
“…It is a common metabolic disorder in general population 2 . The thyroid dysfunction increases with age, especially in women 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Decreased thyroid function not only increases the number of LDL particles but also promote LDL oxidation, thereby increasing the risk of atherosclerosis. 16 HDL was increased in both overt and subclinical hypothyroidism, however, the increase was significant only in case of subclinical hypothyroidism. A study by Packard et al, reported that reduced HDL-C as a powerful predicator for premature coronary heart diseases.…”
Section: Discussionmentioning
confidence: 81%